MICROSTRUCTURE AND PHASE TRANSFORMATION OF PURE TITANIUM DURING NITRIDING PROCESS BY HIGH DENSITY PLASMA - J.M. Windajanti; D.J.D.H. Santjojo; Abdurrouf Abdurrouf (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2017)
Low temperature nitriding process at a temperature of 450 °C has been carried out in order to increase the surface hardness of pure titanium. The plasma nitriding process was utilized by high density RF-DC system with an addition of a hollow cathode device. The plasma was generated by RF generator with the frequency of 2 MHz and attract directly to the cathode plate by high voltage DC bias of -500 to -600 V. The plasma of N2/H2 gases with a flow rate of 160/40 mL/min in gas pressure of 75, 50, and 30 Pa was used in nitriding process for 4 h and 8 h. The occurrence of phase transformation of –Ti to w-Ti triggers the formation of TiN as a nitride layer. The formation of TiN and the diffusion of nitrogen into a titanium matrix can increase the surface hardness of pure titanium up to 792.0 HV.